Silicon-based flame-retardant high-heat-resistance hydrocarbon resin, preparation method thereof and application of silicon-based flame-retardant high-heat-resistance hydrocarbon resin in copper-clad plate preparation

By preparing a silicon-based flame-retardant and heat-resistant hydrocarbon resin, the problem of insufficient flame retardancy and heat resistance of existing hydrocarbon resins in copper-clad laminates is solved, and the overall performance of copper-clad laminates is improved, making it suitable for the manufacture of high-performance circuit boards.

CN120965938APending Publication Date: 2025-11-18DONGCAI ELECTRONIC MATERIALS (MEISHAN) CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510905925.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing hydrocarbon resins have poor flame retardancy, insufficient heat resistance, low glass transition temperature, insufficient rigidity, and large coefficient of thermal expansion in copper clad laminates, which limits their application and development.

Method used

By using silicon-based flame-retardant and heat-resistant hydrocarbon resins, and through unique molecular structure design and synthesis processes, hydrocarbon resins with excellent dielectric properties, outstanding heat resistance, and excellent flame-retardant properties are prepared and applied to the preparation of copper clad laminates.

Benefits of technology

It significantly improves the overall performance of copper clad laminates, possessing excellent dielectric properties, good thermal stability, high mechanical strength, and outstanding flame retardant effect, meeting the material requirements for high-performance circuit board manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005478540510000011
    Figure BDA0005478540510000011
  • Figure BDA0005478540510000022
    Figure BDA0005478540510000022
  • Figure BDA0005478540510000031
    Figure BDA0005478540510000031
Patent Text Reader

Abstract

The invention discloses silicon-based flame-retardant high-heat-resistance hydrocarbon resin as well as a preparation method and application thereof in preparation of a copper-clad plate, and belongs to the technical field of electronic resin synthesis. The preparation method of the silicon-based flame-retardant high-heat-resistance hydrocarbon resin comprises the following steps: S1, adding a first monomer, organic silicon and a catalyst into a reaction container, then adding dehydrated toluene and fully stirring, and after the reaction is finished, carrying out silica gel adsorption, filtration and reduced pressure distillation to obtain a silicon-containing unsaturated monomer; s2, sequentially adding a first monomer, a silicon-containing unsaturated monomer, a second monomer and a third monomer into a reaction container, then adding a solvent A and a cationic initiator, fully stirring, and washing and distilling after the reaction is finished to obtain the silicon-based flame-retardant high-heat-resistance hydrocarbon resin. The prepared silicon-based flame-retardant high-heat-resistance hydrocarbon resin has excellent dielectric property, heat resistance, mechanical strength and flame retardance, and can endow a copper-clad plate with excellent dielectric property, heat resistance, mechanical strength, flame retardance and the like when being applied to preparation of the copper-clad plate.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electronic resin synthesis, in particular to a silicon-based flame-retardant high-heat-resistant hydrocarbon resin, a preparation method thereof and application thereof in the preparation of copper-clad plates. BACKGROUND

[0002] With the rapid development of current artificial intelligence large-scale integrated circuits (AIGC), machine learning, 5G communication, millimeter wave radar, Internet of Things and other industries, the frequency of signal transmission on printed circuit boards is getting higher and higher, and high-frequency high-speed copper-clad plates have become a research hotspot in the current printed circuit board industry. In order to reduce the transmission loss of high-frequency bands, and at the same time be able to cope with high-temperature soldering during substrate installation and high-multilayer assembly requirements, the insulating material used for copper-clad plates needs to have halogen-free flame retardation, better dielectric properties, heat resistance, glass transition temperature and dimensional stability.

[0003] In recent years, hydrocarbon resins such as polybutadiene resin, styrene-butadiene copolymer, ethylene-propylene terpolymer, and cycloolefin copolymer have attracted much attention due to their small molecular chain polarity (the electronegativity of carbon and hydrogen atoms is 2.5 and 2.1, respectively) and excellent dielectric properties (dielectric constant 2.4-2.8 at 1 MHz, tan delta 0.0002-0.0006). However, such hydrocarbon resins have poor flame retardancy, and the chain segment flexibility is extremely large, resulting in poor adhesion to the substrate. The copper-clad plate prepared therefrom has insufficient flame retardancy, and also has the disadvantages of poor heat resistance, low glass transition temperature, insufficient rigidity, and large thermal expansion coefficient, which limits its application and development. SUMMARY

[0004] The present application aims to overcome the shortcomings of the prior art, and provides a silicon-based flame-retardant high-heat-resistant hydrocarbon resin, a preparation method thereof and application thereof in the preparation of copper-clad plates. The silicon-based flame-retardant high-heat-resistant hydrocarbon resin has a unique molecular structure design and synthesis process, and has excellent dielectric properties, outstanding heat resistance, high mechanical strength and reliable flame retardancy. When applied to the preparation of copper-clad plates, the comprehensive performance of the copper-clad plates can be significantly improved, and the copper-clad plates have excellent dielectric properties, good heat stability, high mechanical strength and excellent flame retardancy, thereby providing a high-quality material solution for the manufacture of high-performance circuit boards in the electronic information industry.

[0005] The purpose of the present application is achieved by the following technical solutions:

[0006] A silicon-based flame-retardant high-heat-resistant hydrocarbon resin has a chemical structure general formula shown in formula (I):

[0007]

[0008] Wherein, m, g are any integer in 2-100, n is any integer in 1-20, j is any integer in 1-30;

[0009] R1 is Any one of the following formulae:

[0010] R2 is hydrogen or one-substituted phenyl with 1-4 carbon atoms;

[0011] R3 is any one of ethenyl, isopropenyl, 1-butenyl, 2-butenyl;

[0012] R4, R5, R6 are hydrogen atoms or methyl;

[0013] R7 has any one of the following chemical structure formulae (II-1)-(II-3):

[0014]

[0015] In formulae (II-1)-(II-3), R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 are selected from methyl, ethyl, phenyl, ethenyl;

[0016] At least one of R8, R9, R 10 is ethenyl;

[0017] At least one of R 11 , R 12 , R 13 is ethenyl;

[0018] At least one of R 14 , R 15 , R 16中 is ethenyl;

[0019] The silicon-based flame-retardant high-heat-resistant hydrocarbon resin is a colorless to light yellow transparent liquid with a number average molecular weight of 900-28000 and a weight average molecular weight of 1100-35000.

[0020] Further, in order to achieve the above-mentioned purpose, the application further provides a preparation method of the silicon-based flame-retardant high-heat-resistant hydrocarbon resin, comprising the following steps:

[0021] S1. Preparing a silicon-containing unsaturated monomer:

[0022] The first monomer, organosilicon, and catalyst were added to a reaction vessel, followed by the addition of dehydrated toluene. The mixture was stirred at 70–90 °C for 8–20 h. After the reaction was completed, the mixture was subjected to silica gel adsorption, filtration, and vacuum distillation to obtain a silicon-containing unsaturated monomer.

[0023] S2. Preparation of silicon-based flame-retardant and heat-resistant hydrocarbon resin:

[0024] The first monomer, the silicon-containing unsaturated monomer, the second monomer, and the third monomer were added to the reaction vessel in sequence, followed by the addition of solvent A and a cationic initiator. The reaction was stirred at 20–40°C for 5–8 hours. After the reaction was completed, the product was washed and distilled to obtain a silicon-based flame-retardant high heat-resistant hydrocarbon resin.

[0025] The first monomer is one or two of the general chemical structural formulas shown in formulas (Ⅳ-1) to (Ⅳ-3);

[0026]

[0027] The second monomer is any one or two of styrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-propylstyrene, 3-propylstyrene, 4-propylstyrene, 2-isopropylstyrene, 3-isopropylstyrene, and 4-isopropylstyrene;

[0028] The third monomer is any one or two of butadiene, 2-methyl-1,3-butadiene, 1,4-pentadiene, 1,3-pentadiene, 1,5-hexadiene, and 1,4-hexadiene.

[0029] Preferably, the organosilicon is any one or more of vinyl dimethylsilane, vinyl diethylsilane, vinyl methyl ethylsilane, vinyl diphenylsilane, methyl divinylsilane, and (4-vinylphenyl) dimethylsilane.

[0030] Preferably, the organosilicon has the general chemical structure shown in formula (V):

[0031]

[0032] In equation (V), R 29 R 30 R 31 Selected from methyl, ethyl, phenyl, vinyl or, vinyl, and R 29 R 30 R 31 At least one of them is vinyl or styrene.

[0033] Preferably, the silicon-containing unsaturated monomer has any one or more general chemical structural formulas shown in formulas (Ⅲ-1) to (Ⅲ-4);

[0034]

[0035] In equations (Ⅲ-1) to (Ⅲ-4), R 17 R 18 R 19 R 20 R 21 R 22 R 23 R 24 R 25 R 26 R 27 R 28 Selected from methyl, ethyl, phenyl, and vinyl;

[0036] R 17 R 18 R 19 At least one of them is vinyl;

[0037] R 20 R 21 R 22 At least one of them is vinyl;

[0038] R 23 R 24 R 25 At least one of them is vinyl;

[0039] R 26 R 27 R 28 At least one of them is vinyl.

[0040] Preferably, in step S1, the molar ratio of the first monomer, organosilicon, and catalyst is 1:1:(3.5×10⁻⁶). -5 ~4×10 -4 ).

[0041] Preferably, in step S1, the catalyst is chloroplatinic acid or palladium on carbon.

[0042] Preferably, in step S2, the molar ratio of the first monomer, the silicon-containing unsaturated monomer, the second monomer, and the third monomer is 1:(0.95~1.25):(0.05~0.2):(0.05~0.3).

[0043] Preferably, solvent A is toluene or xylene, and the mass of solvent A is 2 to 10 times the total mass of the first monomer, the silicon-containing unsaturated monomer, the second monomer, and the third monomer.

[0044] Preferably, in step S2, the cationic initiator is any one of boron trifluoride ethyl ether, boron trifluoride ethylamine, methanesulfonic acid, and p-toluenesulfonic acid; the mass of the cationic initiator is 0.01 to 0.11 times the total mass of the first monomer, the silicon-containing unsaturated monomer, the second monomer, and the third monomer.

[0045] Furthermore, to achieve the above objectives, the present invention also discloses the application of silicon-based flame-retardant high-heat-resistant hydrocarbon resin in the preparation of copper-clad laminates, wherein the preparation method of the copper-clad laminate includes the following steps:

[0046] A resin solution is prepared by uniformly mixing 75-100 parts by weight of silicon-based flame-retardant high-heat-resistant hydrocarbon resin, 0-25 parts by weight of high-Tg hydrocarbon resin, 0.01%-0.3% by weight of initiator, 35%-55% by weight of filler, and 34%-36% by weight of solvent B (total hydrocarbon resin and filler). Glass fibers are then immersed in the resin solution, removed, and suspended at room temperature to remove most of the solvent. The fibers are then baked in an oven at 130℃-170℃ for 4-7 minutes to obtain a halogen-free flame-retardant, high-heat-resistant, low-dielectric-loss semi-cured sheet. Several layers of the semi-cured sheet are then stacked, and copper foil is attached to both sides. After hot pressing, natural cooling, and depressurization, a halogen-free flame-retardant, high-heat-resistant, low-dielectric-loss copper-clad laminate is obtained. The total mass of the hydrocarbon resin is the total mass of the silicon-based flame-retardant high-heat-resistant hydrocarbon resin and the high-Tg hydrocarbon resin.

[0047] The high-Tg hydrocarbon resin has the general chemical formula (VI):

[0048]

[0049] In equation (VI), k ranges from 0 to 8, and R... 32 It consists of hydrocarbon groups with 6 to 30 carbon atoms and an aromatic ring structure.

[0050] Preferably, the initiator is any one of dicumyl peroxide (DCP), di-tert-butyl peroxide (DTBP), or tert-butyl peroxide (CP-01).

[0051] Preferably, the filler is any one or more of the following: silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, titanium dioxide, talc, and iron oxide.

[0052] Preferably, solvent B is any one or more of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, and propylene glycol methyl ether acetate.

[0053] Preferably, the fiberglass cloth model is selected from 1080E, 2116, 2313, 3313, and 7628.

[0054] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0055] (1) The silicon-based flame-retardant and heat-resistant hydrocarbon resin of the present invention is composed of three elements: carbon, hydrogen and silicon. It has low molecular polarity and excellent dielectric properties. The molecular structure of the silicon-based flame-retardant and heat-resistant hydrocarbon resin of the present invention contains sufficient vinyl side chains and aromatic ring structures with vinyl groups, which can improve the crosslinking density of the hydrocarbon resin curing and enhance the rigidity of the molecular structure, thereby improving the heat resistance, mechanical strength and dimensional stability of the hydrocarbon resin curing.

[0056] (2) The silicon-based flame-retardant high heat-resistant hydrocarbon resin of the present invention contains an organosilicon structure. The Si-C bond has high thermal stability, which can improve the heat resistance of the hydrocarbon resin. The Si-C bond has low polarity, which can enable the hydrocarbon resin to maintain excellent dielectric properties.

[0057] (3) The silicon-based flame-retardant high heat-resistant hydrocarbon resin of the present invention contains an organosilicon structure, has condensed phase flame-retardant properties, meets the requirements of halogen-free flame retardant resin, and has low hygroscopicity and good performance stability compared with phosphorus-containing flame retardants.

[0058] (4) The resin composition for copper clad laminates of the present invention contains a silicon-based flame-retardant and heat-resistant hydrocarbon resin, which has the performance characteristics of a silicon-based flame-retardant and heat-resistant hydrocarbon resin, namely, excellent heat resistance, mechanical strength, dimensional stability and dielectric properties.

[0059] (5) The resin composition for copper clad laminates of the present invention contains high Tg hydrocarbon resin, which can be composed of two elements, carbon and hydrogen, with low molecular polarity, and can maintain the excellent dielectric properties of silicon-based flame-retardant high heat-resistant hydrocarbon resin, while providing good process flowability and heat resistance.

[0060] (6) The copper-clad laminate prepared by the resin composition for copper-clad laminate provided by the present invention has excellent comprehensive performance: the UL94 performance test reaches the V-0 level, the dielectric constant is 2.44~2.49 at 10GHz, the dielectric loss is ≤0.0011, the glass transition temperature is ≥246℃, and the peel strength is ≥1.49N / mm.

[0061] (7) The preparation process of the present invention is easy to operate, and the prepared silicon-based flame-retardant high heat-resistant hydrocarbon resin and copper-clad laminate resin composition are suitable for the field of high-performance printed circuit boards and have strong practicality. Detailed Implementation

[0062] Part 1: Preparation of Silicon-based Flame-retardant High Heat-resistant Hydrocarbon Resins (Examples 1-4).

[0063] Example 1:

[0064] S1. In a reaction flask equipped with a stirrer, thermometer, and nitrogen, the molar ratio is 1:1:9×10 -51,3-Divinylbenzene, vinyldimethylsilane, and chloroplatinic acid were added sequentially, followed by 2.5 times the total mass of dehydrated toluene of 1,3-divinylbenzene and vinyldimethylsilane. The mixture was heated to 80°C under stirring and maintained at this temperature for 11 hours. After the reaction was completed, the toluene was adsorbed onto silica gel, filtered, and distilled under reduced pressure to obtain a silicon-containing unsaturated monomer.

[0065] S2. In a reaction flask equipped with a stirrer, thermometer, and nitrogen or argon gas, 1,3-divinylbenzene, silicon-containing unsaturated monomer, 2-ethylstyrene, and 2-methyl-1,3-butadiene are added sequentially in a molar ratio of 1:1.05:0.088:0.12. Then, three times the total mass of the four monomers in step S2 (hydrotoluene) and 0.069 times the total mass of the four monomers (boron trifluoride diethyl ether) are added. The mixture is stirred and reacted at 30°C for 8 hours. After the reaction is complete, an appropriate amount of water is added to wash the product four times. The solvent is distilled off under normal pressure until the product content is 70% ± 1%, thus obtaining the silicon-based flame-retardant high heat-resistant hydrocarbon resin of Example 1, with a silicon content of 8.05%. Gel chromatograph analysis shows that the number average molecular weight is 7050 and the weight average molecular weight is 15120.

[0066] Example 2:

[0067] S1. In a reaction flask equipped with a stirrer, thermometer, and nitrogen, the molar ratio is 1:1:9×10 -5 1,3-Divinylbenzene, vinyldimethylsilane, and chloroplatinic acid were added sequentially, followed by 2.5 times the total mass of dehydrated toluene of 1,3-divinylbenzene and vinyldimethylsilane. The mixture was heated to 80°C under stirring and maintained at this temperature for 11 hours. After the reaction was completed, the toluene was adsorbed onto silica gel, filtered, and distilled under reduced pressure to obtain a silicon-containing unsaturated monomer.

[0068] S2. In a reaction flask equipped with a stirrer, thermometer, and nitrogen or argon gas, 1,3-divinylbenzene, silicon-containing unsaturated monomer, 2-ethylstyrene, and 2-methyl-1,3-butadiene are added sequentially in a molar ratio of 1:1.05:0.15:0.2. Then, three times the total mass of the four monomers in step S2 (hydrotoluene) and 0.073 times the total mass of the four monomers (boron trifluoride diethyl ether) are added. The mixture is stirred and reacted at 30°C for 8 hours. After the reaction is complete, an appropriate amount of water is added to wash the product four times. The solvent is distilled off under normal pressure until the product content is 70% ± 1%, thus obtaining the silicon-based flame-retardant high heat-resistant hydrocarbon resin of Synthetic Example 2, with a silicon content of 7.54%. Gel chromatograph analysis shows that the number average molecular weight is 4869 and the weight average molecular weight is 8813.

[0069] Example 3:

[0070] S1. In a reaction flask equipped with a stirrer, thermometer, and nitrogen, the molar ratio is 1:1:9×10 -51,3-Divinylbenzene, (4-vinylphenyl)dimethylsilane, and chloroplatinic acid were added sequentially, followed by 3.8 times the total mass of dehydrated toluene of 1,3-divinylbenzene and (4-vinylphenyl)dimethylsilane. The mixture was heated to 80°C under stirring and maintained at this temperature for 11 hours. After the reaction was completed, the toluene was adsorbed onto silica gel, filtered, and distilled under reduced pressure to obtain a silicon-containing unsaturated monomer.

[0071] S2. In a reaction flask equipped with a stirrer, thermometer, and nitrogen or argon gas, 1,3-diisopropenylbenzene, silicon-containing unsaturated monomer, 2-ethylstyrene, and 2-methyl-1,3-butadiene are added sequentially in a molar ratio of 1:0.97:0.2:0.15. Then, 4 times the total mass of the four monomers in step S2 (hydrotoluene) and 0.084 times the total mass of the four monomers (boron trifluoride diethyl ether) are added. The mixture is stirred and reacted at 40°C for 6 hours. After the reaction is completed, an appropriate amount of water is added to wash the product four times. The solvent is distilled off under normal pressure until the product content is 70% ± 1%, thus obtaining the synthetic example 3, a silicon-based flame-retardant high-heat-resistant hydrocarbon resin with a silicon content of 5.6%. Gel chromatograph analysis shows that the number average molecular weight is 2608 and the weight average molecular weight is 5998.

[0072] Example 4:

[0073] S1. In a reaction flask equipped with a stirrer, thermometer, and nitrogen, the molar ratio is 1:1:9×10 -5 1,3-Divinylbenzene, (4-vinylphenyl)dimethylsilane, and chloroplatinic acid were added sequentially, followed by 3.8 times the total mass of dehydrated toluene of 1,3-divinylbenzene and (4-vinylphenyl)dimethylsilane. The mixture was heated to 80°C under stirring and maintained at this temperature for 11 hours. After the reaction was completed, the toluene was adsorbed onto silica gel, filtered, and distilled under reduced pressure to obtain a silicon-containing unsaturated monomer.

[0074] S2. In a reaction flask equipped with a stirrer, thermometer, and nitrogen or argon gas, 1,3-diisopropenylbenzene, silicon-containing unsaturated monomer, 2-ethylstyrene, and 1,5-hexadiene are added sequentially in a molar ratio of 1:1.2:0.2:0.25. Then, 4.5 times the total mass of the four monomers from step S2 (hydrotoluene) and 0.02 times the total mass of the four monomers (methanesulfonic acid) are added. The mixture is stirred and reacted at 40°C for 5 hours. After the reaction is complete, an appropriate amount of water is added to wash the product 5 times. The solvent is distilled off under normal pressure until the product content is 70% ± 1%, thus obtaining the synthetic example 4, a silicon-based flame-retardant high-heat-resistant hydrocarbon resin with a silicon content of 6.0%. Gel chromatograph analysis shows that the number average molecular weight is 9259 and the weight average molecular weight is 17130.

[0075] Part Two: Preparation of Halogen-Free Flame-Retardant, High-Heat-Resistant, Low-Dielectric-Loss Copper-Clad Laminates (Examples 5-8).

[0076] A resin solution is prepared by uniformly mixing 75-100 parts by weight of silicon-based flame-retardant high heat-resistant hydrocarbon resin, 0-25 parts by weight of high Tg hydrocarbon resin, 0.01%-0.3% by weight of initiator, 35%-55% by weight of filler, and 34%-36% by weight of solvent B (total mass of hydrocarbon resin and filler). Glass fibers are then immersed in the resin solution, removed, and suspended at room temperature to remove most of the solvent. Finally, the fibers are baked in an oven at 130℃-170℃ for 4-7 minutes to obtain a halogen-free flame-retardant, high heat-resistant, and low dielectric loss semi-cured sheet. The total mass of hydrocarbon resin is the total mass of silicon-based flame-retardant high heat-resistant hydrocarbon resin and high Tg hydrocarbon resin.

[0077] Several layers of semi-cured sheets are stacked together, and copper foil is attached to both sides. The sheets are placed in a hot press at a temperature of 150-170°C. Depending on the adhesive flow, the pressure is gradually increased to 0.2-4 MPa, and the vacuum is evacuated to within 50 torr. The sheets are pressed for 0.5-1 hour, and then the temperature is gradually increased to 200-220°C for 4-8 hours. After natural cooling and depressurization, a halogen-free flame-retardant, high heat-resistant, and low dielectric loss copper-clad laminate is obtained.

[0078] The method for preparing the high Tg hydrocarbon resin is provided by patent CN116284692A.

[0079] The components and mass fractions of the halogen-free flame-retardant, high heat-resistant, and low dielectric loss copper-clad laminates in Examples 2-5 are shown in Table 1.

[0080] Table 1:

[0081]

[0082] The general chemical structural formulas of the high-Tg hydrocarbon resins used in Examples 2-5 are as follows:

[0083]

[0084] In the formula, k = 0 to 8, R 32 The product was 4,4'-dimethylbenzene, synthesized according to the method of patent CN116284692A. The synthesized product was detected by gel permeation chromatography (GPC), and the mass fraction of the compound with n=0 was 33%.

[0085] Comparative Example 1:

[0086] 100 parts by weight of polybutadiene resin (Kreville Ricon 130), 0.2 parts by weight of dicumyl peroxide, and (appropriate amount) solvent were uniformly stirred and mixed to prepare an epoxy resin composition for copper clad laminate with a solid content of 64% to 66%. Glass fibers were immersed in the resin composition and then removed. Most of the solvent was removed by hanging at room temperature. The fibers were then baked in an oven at 150°C for 5 minutes to obtain a prepreg. Ten layers of prepreg were stacked together and copper foil was attached to both sides. The prepreg was placed in a hot press at 170°C. The pressure was gradually increased to 3 MPa (depending on the resin flow). The pressure was then reduced to within 50 torr and pressed for 1 hour. The temperature was then gradually increased to 200°C and hot-pressed for 6 hours. After natural cooling and depressurization, the copper clad laminate of Comparative Example 1 was obtained.

[0087] Comparative Example 2:

[0088] 100 parts by weight of butadiene-styrene copolymer (Kreville Ricon 100), 0.15 parts by weight of dicumyl peroxide, and (appropriate amount) solvent were uniformly stirred and mixed to prepare an epoxy resin composition for copper-clad laminate with a solid content of 64% to 66%. Glass fibers were immersed in the resin solution and then removed. Most of the solvent was removed by hanging at room temperature, and then the fibers were baked in an oven at 150°C for 5 minutes to obtain a prepreg. Ten layers of prepreg were stacked together, and copper foil was attached to both sides. The prepreg was placed in a hot press at 170°C. The pressure was gradually increased to 3 MPa (depending on the resin flow), and the vacuum was drawn to within 50 torr for 1 hour. Then the temperature was gradually increased to 200°C and hot-pressed for 6 hours. After natural cooling and depressurization, the copper-clad laminate of Comparative Example 2 was obtained.

[0089] Comparative Example 3:

[0090] 30 parts by weight of butadiene-styrene copolymer (Kreville Ricon 100), 70 parts by weight of silicone flame-retardant high heat-resistant hydrocarbon resin (Synthetic Example 2), 0.15 parts by weight of dicumyl peroxide, and (appropriate amount) solvent were uniformly stirred and mixed to prepare an epoxy resin composition for copper-clad laminate with a solid content of 64% to 66%. Glass fibers were immersed in the resin solution and then removed. Most of the solvent was removed by hanging at room temperature. The fibers were then baked in an oven at 150°C for 5 minutes to obtain a prepreg. Ten layers of prepreg were stacked together, and copper foil was attached to both sides. The prepreg was placed in a hot press at 170°C. The pressure was gradually increased to 3 MPa (depending on the resin flow), and the vacuum was drawn to within 50 torr for 1 hour. The temperature was then gradually increased to 200°C for 6 hours. After natural cooling and depressurization, the copper-clad laminate of Comparative Example 3 was obtained.

[0091] Comparative Example 4:

[0092] 70 parts by weight of butadiene-styrene copolymer (Kreville Ricon 100), 30 parts by weight of silicone flame-retardant high heat-resistant hydrocarbon resin (Synthetic Example 2), 0.15 parts by weight of dicumyl peroxide, and (appropriate amount) solvent were uniformly stirred and mixed to prepare an epoxy resin composition for copper-clad laminate with a solid content of 64% to 66%. Glass fibers were immersed in the resin solution and then removed. Most of the solvent was removed by hanging at room temperature, and then the fiber was baked in an oven at 150°C for 5 minutes to obtain a prepreg. Ten layers of prepreg were stacked together, and copper foil was attached to both sides. The prepreg was placed in a hot press at 170°C. The pressure was gradually increased to 3 MPa (depending on the resin flow), and the vacuum was drawn to within 50 torr for 1 hour. Then the temperature was gradually increased to 200°C and hot-pressed for 6 hours. After natural cooling and depressurization, the copper-clad laminate of Comparative Example 4 was obtained.

[0093] The performance parameters of the copper-clad laminates prepared in Examples 5-8 and the copper-clad laminates in Comparative Examples 1-4 are compared, as shown in Table 2.

[0094] Table 2:

[0095]

[0096]

[0097] As can be seen from Table 2, the copper-clad laminate made from the halogen-free flame-retardant, high heat-resistant, and low dielectric loss copper-clad laminate provided in this application has halogen-free flame-retardant properties and excellent dielectric properties, heat resistance, dimensional stability, and peel strength.

[0098] Compared with Examples 5-8, Comparative Examples 1-4 used hydrocarbon resins such as polybutadiene and butadiene-styrene copolymer to prepare copper-clad laminates, resulting in copper-clad laminates with poor heat resistance, dimensional stability and peel strength. Adding synthetic hydrocarbon resin to Comparative Examples 3-4 can improve the flame retardancy, heat resistance, dimensional stability and peel strength of copper-clad laminates.

[0099] The relevant standards used for the technical specifications in this article are as follows:

[0100] Glass transition temperature Tg: determined by dynamic thermomechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;

[0101] Dielectric constant Dk and dielectric loss Df: 10GHz data were tested using the SPDR method according to the method specified in IEC 61189-2-721;

[0102] CTE (Z-axis coefficient of thermal expansion): Tested according to the method specified in 2.4.24.5 of IPC-TM-650;

[0103] Peel strength: The peel strength of the metal capping layer was tested according to the test conditions for "thermal stress" specified in 2.4.8 of IPC-TM-650.

[0104] UL 94 flame retardancy test: determined according to the UL 94 vertical burning test method.

Claims

1. A silicon-based flame-retardant, high-heat-resistant hydrocarbon resin, characterized in that, Having the general chemical structural formula shown in formula (Ⅰ): Where m and g are any integers from 2 to 100, n is any integer from 1 to 20, and j is any integer from 1 to 30; R1 is Any one of them; R2 is hydrogen or a monosubstituted phenyl group with an alkyl group having 1 to 4 carbon atoms; R3 is any one of vinyl, isopropenyl, 1-butenyl, and 2-butenyl; R4, R5, and R6 are all hydrogen atoms or methyl groups; R7 has any of the general chemical structural formulas (Ⅱ-1) to (Ⅱ-3): In equations (Ⅱ-1) to (Ⅱ-3), R8, R9, R 10 R 11 R 12 R 13 R 14 R 15 R 16 Selected from methyl, ethyl, phenyl, and vinyl; R8, R9, R 10 At least one of them is vinyl; R 11 R 12 R 13 At least one of them is vinyl; R 14 R 15 R 16中 At least one of them is vinyl.

2. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 1, characterized in that, Includes the following steps: S1. Preparation of silicon-containing unsaturated monomers: The first monomer, organosilicon, and catalyst were added to a reaction vessel, followed by the addition of dehydrated toluene. The mixture was stirred at 70–90 °C for 8–20 h. After the reaction was completed, the mixture was subjected to silica gel adsorption, filtration, and vacuum distillation to obtain a silicon-containing unsaturated monomer. S2. Preparation of silicon-based flame-retardant and heat-resistant hydrocarbon resin: The first monomer, the silicon-containing unsaturated monomer, the second monomer, and the third monomer were added to the reaction vessel in sequence, followed by the addition of solvent A and a cationic initiator. The reaction was stirred at 20–40°C for 5–8 hours. After the reaction was completed, the product was washed and distilled to obtain a silicon-based flame-retardant high heat-resistant hydrocarbon resin. The first monomer is one or two of the general chemical structural formulas shown in formulas (Ⅳ-1) to (Ⅳ-3); The second monomer is any one or two of styrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-propylstyrene, 3-propylstyrene, 4-propylstyrene, 2-isopropylstyrene, 3-isopropylstyrene, and 4-isopropylstyrene; The third monomer is any one or two of butadiene, 2-methyl-1,3-butadiene, 1,4-pentadiene, 1,3-pentadiene, 1,5-hexadiene, and 1,4-hexadiene.

3. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 2, characterized in that, The organosilicon is any one or more of vinyl dimethylsilane, vinyl diethylsilane, vinyl methyl ethylsilane, vinyl diphenylsilane, methyl divinylsilane, and (4-vinylphenyl) dimethylsilane.

4. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 2, characterized in that, The organosilicon has the general chemical structure shown in formula (V): In equation (V), R 29 R 30 R 31 Selected from methyl, ethyl, phenyl, vinyl or, vinyl, and R 29 R 30 R 31 At least one of them is vinyl or styrene.

5. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 2, characterized in that, The silicon-containing unsaturated monomer has any one or more general chemical structural formulas shown in formulas (Ⅲ-1) to (Ⅲ-4); In equations (Ⅲ-1) to (Ⅲ-4), R 17 R 18 R 19 R 20 R 21 R 22 R 23 R 24 R 25 R 26 R 27 R 28 Selected from methyl, ethyl, phenyl, and vinyl; R 17 R 18 R 19 At least one of them is vinyl; R 20 R 21 R 22 At least one of them is vinyl; R 23 R 24 R 25 At least one of them is vinyl; R 26 R 27 R 28 At least one of them is vinyl.

6. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 2, characterized in that, In step S1, the molar ratio of the first monomer, organosilicon, and catalyst is 1:1:(3.5×10⁻⁶). -5 ~4×10 -4 ).

7. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 2, characterized in that, In step S1, the catalyst is chloroplatinic acid or palladium on carbon.

8. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 2, characterized in that, In step S2, the molar ratio of the first monomer, the silicon-containing unsaturated monomer, the second monomer, and the third monomer is 1:(0.95~1.25): (0.05~0.2):(0.05~0.3)。 9. The method for preparing the silicon-based flame-retardant high heat-resistant hydrocarbon resin according to claim 2, characterized in that, In step S2, the cationic initiator is any one of boron trifluoride ethyl ether, boron trifluoride ethylamine, methanesulfonic acid, and p-toluenesulfonic acid.

10. The application of the silicon-based flame-retardant, high-heat-resistant hydrocarbon resin according to claim 1 in the preparation of copper-clad laminates, characterized in that, The method for preparing the copper-clad laminate includes the following steps: A resin solution is prepared by uniformly mixing 75-100 parts by weight of silicon-based flame-retardant high-heat-resistant hydrocarbon resin, 0-25 parts by weight of high-Tg hydrocarbon resin, 0.01%-0.3% by weight of initiator, 35%-55% by weight of filler, and 34%-36% by weight of solvent B (total hydrocarbon resin and filler). Glass fibers are then immersed in the resin solution, removed, and suspended at room temperature to remove most of the solvent. The fibers are then baked in an oven at 130℃-170℃ for 4-7 minutes to obtain a halogen-free flame-retardant, high-heat-resistant, low-dielectric-loss semi-cured sheet. Several layers of the semi-cured sheet are then stacked, and copper foil is attached to both sides. After hot pressing, natural cooling, and depressurization, a halogen-free flame-retardant, high-heat-resistant, low-dielectric-loss copper-clad laminate is obtained. The total mass of the hydrocarbon resin is the total mass of the silicon-based flame-retardant high-heat-resistant hydrocarbon resin and the high-Tg hydrocarbon resin. The high-Tg hydrocarbon resin has the general chemical formula (VI): In equation (VI), k ranges from 0 to 8, and R... 32 It consists of hydrocarbon groups with 6 to 30 carbon atoms and an aromatic ring structure.

Citation Information

Cited By

  • Polydivinylbenzene flame-retardant resin as well as preparation method and condensate thereof

    CN121851229A

  • A polydivinylbenzene flame retardant resin, a method for preparing the same, and a cured product thereof

    CN121851229B